2011
DOI: 10.1213/ane.0b013e318224ac35
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Spinal Cord Ischemia/Reperfusion Injury with Simvastatin in Rats

Abstract: Simvastatin treatment can attenuate hindlimb motor dysfunction and histopathological changes in spinal cord ischemia/reperfusion injury in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
26
1
2
Order By: Relevance
“…Spinal cord ischemia is characterized by degeneration of the gray matter, especially anterior horn cells. 15,16 However, these findings were not observed in our study. Therefore, epinephrine, even when used at 0.5 mg/mL, did not induce marked spinal cord ischemia in rats.…”
Section: Discussioncontrasting
confidence: 92%
“…Spinal cord ischemia is characterized by degeneration of the gray matter, especially anterior horn cells. 15,16 However, these findings were not observed in our study. Therefore, epinephrine, even when used at 0.5 mg/mL, did not induce marked spinal cord ischemia in rats.…”
Section: Discussioncontrasting
confidence: 92%
“…The neurological manifestations were associated with strong evidence of lipid peroxidation. Evidence of oxidative stress included the significant increase in serum TNF-α level and spinal cord homogenate levels of PGE 2 and MDA in addition to AOPP and SOD activity with a significant reduction in CAT activity. The neurological deficits and their strong association with the markers of oxidative stress and inflammation have been strongly documented in previous studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional strategies for preventing paraplegia due to spinal cord ischemia provide insufficient protection and cause additional side effects [2]. The pathophysiological mechanisms of neuronal damage during SC-IRI involve the production of free radicals, lipid peroxidation, intracellular calcium deposition, and apoptosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these drugs have benefits other than lowering lipids, such as anti-inflammatory effect (Yin et al, 2007), antioxidant (Di Napoli et al, 2001), improvement of endothelial function (O'Driscoll et al, 1997) and regulation of neurotrophic levels (Wu et al, 2008). The neuroprotective effect of simvastatin in in vivo models of the brain (Balduini et al, 2003), peripheral nerve (Gholami et al, 2008), and spinal cord (Saito et al, 2011) injuries have also been reported. So, statins are being tested for their potential efficacy in treatment after brain injury (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%